Impacts of Pay-As-You-Throw and Other Residential Solid Waste Policy Options: Southern Maine 2007–2013 - Blackmer, Travis; Criner, George (Maine Policy Review, 2014)
Municipal solid waste management in the U.S. began a transformation in the 1980s as a result of a U.S. Environmental Protection Agency regulation requiring the closure of municipal “dumps.” This legislation, coupled with increasing total and per capita waste, resulted in waste management receiving national attention. Maine and other states began broad efforts to reduce and wisely manage their municipal solid wastes. Many states established solid waste goals, with Maine targeting a waste diversion rate of 50 percent. Four common residential waste management programs in Maine include curbside trash collection, curbside recyclable collection, single-stream recycling, and pay-as-you-throw programs. This article provides estimated impacts from these programs. Pay-as-you-throw, curbside collection of recyclables and single-stream recycling are found to increase the percentage of recycling, while curbside trash collection is found to decrease the percentage of recycling.
Keywords: Maine; solid waste management; municipal solid waste; recycling; pay-as-you-throw